Directors’ Files, Isaiah Bowman - Stefansson, Vilhjalmur, 1879-1962; Bowman, Isaiah, 1878-1950 (1918)
Correspondence between Isaiah Bowman and the Arctic explorer, Vilhjalmur Stefansson. Includes correspondence regarding Stefansson's manuscripts and contributions to the Geographical Review with articles about the Arctic, newspaper article clippings, "Wrangel Island (Copied from 'The Geographical Journal' The Royal Society of Great Britain for December, 1923)," brochures about Stefansson and "The Adventure of Wrangel Island," and a plan for Greenland expedition. Also includes "Canada House of Commons Debates, Official Report-Unrevised Edition, Vol. LX, Wednesday, June 10, 1925, No. 84, however, only the first page was scanned.